Synthesis of Heterogeneous Copper Catalyst Based on Amino-Functionalized Triazine Rings Supported by Silica-Gel for Oxidation of Alcohols - Majid Kolahdoozan; Roozbeh Javad Kalbasi; Mahshid Hossaini (Journal of Chemistry)
Amino-functionalized triazine supported on silica-gel was prepared. This new triazine derivate was applied as a coordinating agent for copper (II) and was characterized by different methods. The copper (II) content of the material was determined by atomic absorption. This novel transition metal supported on heterogeneous surface was used as an effective catalyst for oxidation of benzylic alcohols in the presence of H2O2. This catalyst can be reused without any significant loss of activity.